ANALISIS FAKTOR-FAKTOR KESALAHAN EDITING BERITA PADA WARTAWAN MEDIA CETAK DI PT X - Kusumaningtyas Windi Astuti; Baju Widjasena; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2017)
Society always need of information and education which update. Information obtained through the mass media on newspaper. Editing errors are errors that often occur in the print media that can be detrimental to the company. This study aimed to analyze the factors of news editing error in the print media journalists in PT X. This study is a descriptive qualitative research method with the calculation of reliability HEART and NASA TLx to measuring subjective mental workload journalist. The subjects of this research were 5 people as a key informants and 2 as an triangulation informants. For triangulation subjects taken from the Manager Editorial and Head Editorial. The results of this research from NASA TLx that editor jobs included in the heavy mental workload in which 60% of informants. The HEP value by HEART  method obtained is take and selection news (0.825), distribution to desk (0.821), editing news (0,645).The results showed that the editing process is often experienced that the accuracy of the presentation of news, all of the informants claimed to have encountered an error editing, working time and training factors affecting journalistic editing capabilities while the pressure of time and means factors do not affect the ability of news editing. Analysis workloads including large editorial with the largest category is effort 294. Company X needs to provide regular evaluation and journalism training to increase the ability and capacity of editing news journalist.